The Combined Effect of Caseinates, Native or Heat-Treated Whey Proteins, and Cryogel Formation on the Characteristics of Kefiran Films - Nikoletta Pouliou; Eirini Chrysovalantou Paraskevaidou; Athanasios Goulas; Stylianos Exarhopoulos; Georgia Dimitreli (Molecules)
Kefiran, the extracellular polysaccharide produced from the Generally Recognized as Safe (GRAS) bacteria in kefir grains, with its well-documented functional and health-promoting properties, constitutes a promising biopolymer with a variety of possible uses. Its compatibility with other biopolymers, such as milk proteins, and its ability to form standalone cryogels allow it to be utilized for the fabrication of films with improved properties for applications in the food and biomedical–pharmaceutical industries. In the present work, the properties of kefiran films were investigated in the presence of milk proteins (sodium caseinate, native and heat-treated whey proteins, and their mixtures), alongside glycerol (as a plasticizer) and cryo-treatment of the film-forming solution prior to drying. A total of 24 kefiran films were fabricated and studied for their physical (thickness, moisture content, water solubility, color parameters and vapor adsorption), mechanical (tensile strength and elongation at break), and optical properties. Milk proteins increased film thickness, solubility and tensile strength and reduced water vapor adsorption. The hygroscopic effect of glycerol was mitigated in the presence of milk proteins and/or the application of cryo-treatment. Glycerol was the most effective at reducing the films’ opacity. Heat treatment of whey proteins proved to be the most effective in increasing film tensile strength, reducing, at the same time, the elongation at break, while sodium caseinates in combination with cryo-treatment resulted in films with high tensile strength and the highest elongation at break. Cryo-treatment, carried out in the present study through freezing followed by gradual thawing of the film-forming solution, proved to be the most effective factor in decreasing film roughness. Based on our results, proper selection of the film-forming solution composition and its treatment prior to drying can result in kefiran–glycerol films with favorable properties for particular applications.